The Influence of Price, Product Quality, and Brand Image on Customer Retention Moderated by Supply Chain and After Sale Services - Zakarsyi Zakarsyi; Michael Christian (Dinasti Publisher, 2024)
Sustainable business is a challenge for entrepreneurs. In a highly competitive era, foresight, agility, and analysis are needed in running a business. Companies must be observant in assessing the use of opportunities, agile in running a business, namely focusing on consumer needs, and analysing the company's overall performance. This study aims to analyse variables such as: product price, product quality, brand image, customer retention, supply chain and after sales service. The purpose of this study is to measure and see the factors that influence customer retain. This research is quantitative research and uses primary data conducted by data collection methods in the form of questionnaires from respondents who take a minimum sample of 100. Data collection was carried out by distributing questionnaires online. The data analysis technique uses structural equation modelling (SEM) with PLS (Partial Least Square) software by testing data quality with validity and reliability tests. As well as classical assumption tests and hypothesis testing in this study.